2015
DOI: 10.1111/apt.13474
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the prevalence of Helicobacter pylori and the incidence of gastric cancer across Europe

Abstract: SUMMARY BackgroundThere is little up-to-date review evidence on the prevalence of Helicobacter pylori across Europe. AimTo establish regional and national patterns in H. pylori prevalence across Europe. Secondly, to establish trends over time in H. pylori prevalence and gastric cancer incidence and, thirdly, to report on the relationship between H. pylori prevalence and age group across Europe. MethodsA review of H. pylori prevalence from unselected surveys of adult or general populations across 35 European co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 55 publications
5
63
1
1
Order By: Relevance
“…pylori [12]. However, the prevalence of this present study is lower than report from Ghana which recorded a prevalence of 75.4% among dyspeptic patients [4], reports from Saudi Arabia and Kuwait showing the prevalences of 68% and 62%, respectively [14,15].…”
Section: Discussioncontrasting
confidence: 80%
“…pylori [12]. However, the prevalence of this present study is lower than report from Ghana which recorded a prevalence of 75.4% among dyspeptic patients [4], reports from Saudi Arabia and Kuwait showing the prevalences of 68% and 62%, respectively [14,15].…”
Section: Discussioncontrasting
confidence: 80%
“…Yet, most studies assessing the incidence from earlier periods have found similar results as in the present study, i.e., a stable incidence in gastric cardia cancer, whereas the incidence of non-cardia gastric cancer has declined [11][12][13][14]. A recent comprehensive review of European countries showed a mean annual reduction in the incidence of gastric cancer of 2.1% in Europe from 1993 to 2007 with little variation between countries [15]. Globally, a study using data from Cancer Incidence in five continents from 2003 to 2007 reported an annual decrease of approximately 3% in Europe, Japan and Korea and 2% in North and Latin America [14].…”
Section: Discussionsupporting
confidence: 87%
“…Other studies described a prevalence rate of 30-40 % in US adults and a 60-70 % infection rates in immigrant populations and those of lower socioeconomic status and living under crowded circumstances [3,4]. Resistance to clarithromycin, one of the components of recommended first-line therapy, has been increasing, with 10-15 % resistance in 2004 [5] and *30 % resistance reported in the article by Park et al [6] in this issue of Digestive Diseases and Sciences.…”
Section: Background and Significancementioning
confidence: 99%